Real-time procedural modeling of fracture of brittle materials in games - Sheikh Dawood Abdul Ajees (2009)
This thesis addresses the problem of dynamically modeling fracture of brittle objects in next-generation games. The challenges of this research are to implement a fracture framework in real-time and that produces results that are visually realistic. An image- based procedural approach is proposed since speed and memory usage are important factors in a commercial game system. The criteria for fracture depend on the strength of the impact force and position of the impact point. The crack patterns are based on a probability texture that defines the weak areas of the object where the crack propagates. The probability textures are different for various materials and are specifically designed by the user. Our technique is unique and allows the user to have more control over the shape of the fragments for different types of objects. The results presented demonstrate that the fragments can be dynamically generated in real-time.